2015
DOI: 10.1007/s12262-015-1327-3
|View full text |Cite
|
Sign up to set email alerts
|

Effective and Economic Offloading of Diabetic Foot Ulcers in India with the Bohler Iron Plaster Cast

Abstract: Economic constraints are a major obstacle to the implementation of offloading casts in India. The aim of this study is to monitor the healing and activity limitations related to Bohler iron plaster cast (BIPC) when used for offloading diabetic neuropathic plantar foot ulcers. Thirty patients were cast for 1 month and evaluated for healing using the Pressure Ulcer Scale for Healing (PUSH), and for activity limitation using the Lower Extremity Functional Scale (LEFS). The change in the scores after intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…A validation set of 30 publications was created, including key studies known to the authors published since our previous search (July 29, 2014) . Using this set, the search strings used were validated; ie, each publication had to be identified before the search strings were used in this systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…A validation set of 30 publications was created, including key studies known to the authors published since our previous search (July 29, 2014) . Using this set, the search strings used were validated; ie, each publication had to be identified before the search strings were used in this systematic review.…”
Section: Methodsmentioning
confidence: 99%
“…A study on the topic in LMICs represents a seminal contribution; this study unequivocally demonstrated that applying total contact casts significantly reduced the healing time and the incidence of major amputations among Indian patients grappling with DFUs. 49 …”
Section: Importance Of Early Intervention and Adequate Care Of Dfu; E...mentioning
confidence: 99%
“…this study unequivocally demonstrated that applying total contact casts significantly reduced the healing time and the incidence of major amputations among Indian patients grappling with DFUs. 49 Furthermore, another noteworthy study conducted in resourcelimited settings within India investigated the cost-effectiveness of offloading DFUs through the use of removable cast walkers. The findings of this study substantiated the merits of this approach, revealing remarkable enhancements in healing rates and a reduction in amputation rates among patients who availed themselves of removable cast walkers in comparison to those relying on traditional footwear or no offloading devices.…”
Section: Role Of Various Health Care Professionalsmentioning
confidence: 99%
“…23 This offloading technique aids in healing by reducing the elevated plantar pressure and redistributing forces. 24 The pressure could thus be offloaded from the foot and redistributed to the shin or the upper part of the leg.…”
Section: Introductionmentioning
confidence: 99%